Advancing Food Security with Farmed Edible Insects: Economic, Social, and Environmental Aspects - José E. Aguilar-Toalá; Abraham M. Vidal-Limón; Andrea M. Liceaga (Insects)
Farmed edible insects are considered a potential resource to help address food security concerns toward the year 2050. The sustainability (e.g., lower environmental impact), nutritional (e.g., high-quality proteins, essential amino acids, fiber, unsaturated fats, vitamins, and minerals) and health (e.g., antioxidant, antihypertensive, anti-inflammatory, antimicrobial, and immunomodulatory) benefits are the main reasons for the rise in interest for insects as alternative protein sources for food and feed production. Thus, edible insects can address the future global protein demand of an ever-increasing world population. In this context, several aspects related to their sustainability have been explored and addressed from an environmental perspective. This review describes the rationale for using insects as alternative protein sources and provides a comprehensive viewpoint, integrating economic, environmental, and social aspects into their sustainability framework toward addressing food insecurity concerns. For example, edible insects offer a more sustainable protein source comparable to, or even better than, that of conventional livestock. Considering their sustainability advantages, insects are noted for their lower impact on natural resources (e.g., water and agrarian land) and lower greenhouse gas emissions (e.g., carbon dioxide and methane). From a socioeconomic point of view, edible insects have lower production costs compared to conventional animal protein sources because of their high feed efficiency conversion, rapid growth rate, and short life cycles. Currently, the market for edible, farmed insects is becoming a significant economic activity that not only meets the needs of industry and consumers but also supports the ability of future generations to maintain a secure and sustainable community.